Development of LAMP-Lateral Flow Immunoassay for diagnosis of melioidosis - Najomtien, Priyapa; Potisap, Chotima; Chattagul, Supaksorn; W. Sermswan , Rasana; Wongratanacheewin, Surasak (Srinagarind Medical Journal, 2024)
Background and Objective: Melioidosis is a fatal disease caused by a gram-negative bacterium, Burkholderia pseudomallei. Patients with septicemic melioidosis die within 48 hours, the rapid diagnosis using blood samples is essential. The aim of this study was to develop a loop-mediated isothermal amplification (LAMP) combined with a lateral flow dipstick (LFD) assays for the detection of B. pseudomallei. Methods: The wcbG gene, a putative capsular polysaccharide biosynthesis protein gene of B. pseudomallei was selected for LAMP primers design. Four primers and 1 probe were considered using Primer Explorer software. The conditions for LAMP-LFD were optimized. The sensitivity of LAMP-LFD was investigated with 50 ng to 500 fg of B. pseudomallei genomic DNA while the specificity was evaluated by using 50 ng of 12 bacterial strains. The LAMP-LFD method was evaluated by the spiked 106 CFU to 1 CFU of B. pseudomallei into the normal EDTA blood samples. Results: The LAMP-LFD was successfully developed using 1M betaine, 60°C for 60 min for LAMP cycles and conditions for hybridization with FITC-probe were at 60°C for 5 min. It gave sensitivity of 5 pg/ml and 100% specificity when tested with B. thailandensis, Staphylococcus aureus, S. epidermidis, Escherichia coli, Salmonella group B, Pseudomonas aeruginosa and Klebsiella pneumonia. The detection limit was genomic DNA of 102 CFU per 200 μl of EDTA blood. Conclusion: Our LAMP-LFD assay provided a highly sensitive and specific method to detect B. pseudomallei in the blood based on wcbG gene. It will be another approach for rapid diagnosis of melioidosis.